Comparative proteomics of Shigella flexneri 2a strain 301 using a rabbit ileal loop model reveals key proteins for bacterial adaptation in host niches. (November 2015) - Liu, Xingming; Lu, Lilan; Liu, Xiankai; Pan, Chao; Feng, Erling; Wang, Dongshu; Zhu, Li; Wang, Hengliang
Highlights: A proteomic analysis of Shigella flexneri in different parts of rabbit intestines was performed. Shigella flexneri sensed and responded to the intestinal microenvironment. The abundance of nine proteins changed when bacteria were incubated in vivo. Some proteins were associated with anaerobic fermentation and ROS resistance. Three proteins may participate in a process similar to biofilm formation. Summary: Objectives: Many studies focusing on changes in the host following Shigella spp invasion have been reported in recent years. However, the key factors required for the adaptation of these pathogens to host niches have usually been neglected. Methods: In this study, a comparative proteomic analysis was performed to examine changes in the protein expression profile of Shigella flexneri within the host using a rabbit ileal loop model to reveal proteins that are associated with pathogenic adaptation. Results: The protein expression profiles of bacteria isolated from the ileum and colon were very similar, although they differed slightly from that of bacteria isolated from the cecum. When compared with the sample in vitro, the expressions of seven proteins were found to be upshifted in vivo (OmpA, YgiW, MglB, YfiD, MetK, TktA, and AhpF), while two proteins were down-regulated (ElaB and GlnH). Conclusions: The abundance of nine proteins changed in vivo, suggesting that these proteins may contribute to adaptation to the intestinal lumen.